Assessment of the Adequacy of Volume Load in Craniotomies for Brain Lesions in Children (Herald of the National Children's Medical Center, 2025)
Craniotomy for primary brain lesions in children is considered one of the specific challenges of anesthesia. One of the main goals of anesthesia is to optimize intracranial pressure and maintain cerebral perfusion pressure. This ensures adequate oxygen delivery to brain tissue and, at the same time, prevents secondary brain injury. In neurosurgery, optimizing intraoperative infusion therapy has a significant effect on early awakening, hemodynamic stability, and postoperative recovery. Studies on the use of pulse pressure variation (PPV) in neurosurgical patients remain insufficient, and its impact on infusion therapy, hemodynamic stability, and tissue perfusion under central venous pressure monitoring has not been fully evaluated. Neurosurgical operations for brain tumor removal may carry a risk of hypovolemia for various reasons, including inadequate control of fluid infusion, physiologically compensated arterial hypertension, and treatment with osmotic diuretics. Formula-based fluid management is considered ineffective in neuro-oncological surgeries. Individualized “goal-directed infusion therapy” has been proven to improve postoperative outcomes (Gan T.J., Sopitt A., Maruf M., El-Moalem H., Robertson K.M., Moretti E. Anesthesiology. 2022;02(4):820–26).
Keywords: oncology; neurosurgery; infusion therapy; pulse pressure variation; osmodiuretics; CVP; PPV pediatrics